2017
DOI: 10.1007/s10904-017-0750-2
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Catalytic Activity of Biosynthesized CuO Nanoparticles Using Extract of Galeopsidis herba

Abstract: The main objective of this study was synthesis of CuO nanoparticles using extract of Galeopsidis herba and were characterized by UV-Vis spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy (SEM), SEM with EDS profile and transmission electron microscopy (TEM) analysis. SEM images confirmed that synthesized nanoparticles were spherical in nature. EDS profile confirmed the signal characteristic of cooper and oxygen. All the analyses revealed that synthesized CuO nanoparticles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 35 publications
4
25
0
Order By: Relevance
“…Murali et al ( 2017) also conducted research on ZnO NPs, which had a maximum wavelength of 320 nm. Dobrucka (2018) has also reported that biosynthesized CuO NPs using the extract of Galeopsidis herba had a maximum wavelength of 296 nm. The levan modification of metal ions was confirmed using FTIR.…”
Section: Synthesis and Characterization Of Levan-based Metal Ion Nanoparticlesmentioning
confidence: 98%
“…Murali et al ( 2017) also conducted research on ZnO NPs, which had a maximum wavelength of 320 nm. Dobrucka (2018) has also reported that biosynthesized CuO NPs using the extract of Galeopsidis herba had a maximum wavelength of 296 nm. The levan modification of metal ions was confirmed using FTIR.…”
Section: Synthesis and Characterization Of Levan-based Metal Ion Nanoparticlesmentioning
confidence: 98%
“…It was reported that plant extracts showed numerous advantages, such as availability, safety handling and viability of metabolites. Moreover, the reaction media for the synthesis of inorganic NPs is more interesting over other microorganisms as well as less hazard than other organisms [14].…”
Section: Introductionmentioning
confidence: 99%
“…The floral extract of Magnolia champaca has antiulcer, antidiabetic and anti-inflammatory properties and hence used for the treatment of ulcer, skin disease and wounds [11,12] . Rajshree Sinha et al performed scavenging activity of reduced power assay on a floral extract of Magnolia champaca is a higher percentage of inhibition 90.20% in comparison with ascorbic acid [13,14]. Bangladeshi medicinal plants which are generally utilized in various sicknesses are also assessed for antioxidant activity via DPPH and ABST analysis [15].…”
Section: Introductionmentioning
confidence: 99%